2014
DOI: 10.1371/journal.pone.0098551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NAD(P)H Quinone Oxidoreductase Activity in Azoreductases from P. aeruginosa: Azoreductases and NAD(P)H Quinone Oxidoreductases Belong to the Same FMN-Dependent Superfamily of Enzymes

Abstract: Water soluble quinones are a group of cytotoxic anti-bacterial compounds that are secreted by many species of plants, invertebrates, fungi and bacteria. Studies in a number of species have shown the importance of quinones in response to pathogenic bacteria of the genus Pseudomonas. Two electron reduction is an important mechanism of quinone detoxification as it generates the less toxic quinol. In most organisms this reaction is carried out by a group of flavoenzymes known as NAD(P)H quinone oxidoreductases. Az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 84 publications
0
50
0
Order By: Relevance
“…As reviewed by Ryan (2017) and Koppel et al (2017), there are very few NQOs characterized from human gut bacterial strains. Recently, Ryan et al (2014) identified the NAD(P)H quinone oxidoreductase activity in azoreductase from P. aeruginosa and demonstrated that the azoreductases and the NAD(P)H quinone oxidoreductases belong to the same FMN-dependent azoreductase superfamily.…”
Section: Azoreductase Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed by Ryan (2017) and Koppel et al (2017), there are very few NQOs characterized from human gut bacterial strains. Recently, Ryan et al (2014) identified the NAD(P)H quinone oxidoreductase activity in azoreductase from P. aeruginosa and demonstrated that the azoreductases and the NAD(P)H quinone oxidoreductases belong to the same FMN-dependent azoreductase superfamily.…”
Section: Azoreductase Classificationmentioning
confidence: 99%
“…1 Azoreduction mechanism of amaranth dye by azoreductase enzyme: The UV-Visible spectrum demonstrating the complete reduction of amaranth dye in 24 h of incubation with purified azoreductase. Blue spectrum was recorded at zero time and green was recorded at 24 h oxidoreductases from homo sapiens and human gut bacteria (Liu et al 2008;Ryan et al 2014). …”
Section: Azoreductase Classificationmentioning
confidence: 99%
“…Convergent evolution of azoreductases and quinone reductases has been proposed based on similar reaction mechanisms involving the flavin-mediated reduction of an organic molecule with NAD(P)H and substrate scope (37,38). The lack of enzymatic activity with the azo dye methyl red indicates that PA1024 is not an azoreductase.…”
Section: Exx(t//s)xlhxrxhxn(t/s)xr(v/i)mentioning
confidence: 99%
“…The lack of enzymatic activity with the azo dye methyl red indicates that PA1024 is not an azoreductase. Although there are several azoreductases from P. aeruginosa capable of reducing quinones (38), WrbA is the only other two-electron NAD(P)H: quinone reductase identified to date that does not possess azoreductase activity (39) beside PA1024.…”
Section: Exx(t//s)xlhxrxhxn(t/s)xr(v/i)mentioning
confidence: 99%
“…The PA1225 gene is monocistronic, but any direct binding of PA4203 to the upstream intergenic region was ruled out in this study, suggesting that the effect might be due to the overexpression of nmoA. In a recent publication, Ryan et al suggested that the PA1225 protein is a soluble quinone reductase involved in the detoxification of quinones by their reduction to quinols (43). Further work will be needed to investigate the function of this dehy-…”
Section: Discussionmentioning
confidence: 81%